Architecture and Resilience Interdisciplinary Dialogues - Trogal, Kim; Bauman, Irena; Lawrence, Ranald; Petrescu, Doina (Taylor & Francis, 2018)
Resilience will be a defining quality of the twenty-first century. As we witness the increasingly turbulent effects of climate change, the multiple challenges of resource depletion and wage stagnation, we know that our current ways of living are not resilient. Our urban infrastructures, our buildings, our economies, our ways of managing and governing are still too tightly bound to models of unrestrained free-market growth, individualism and consumerism. Research has shown that the crises arising from climate change will become increasingly frequent and increasingly severe. It is also known that the effects of climate change are not evenly distributed across places and people, and neither are the resources needed to meet these challenges. We will need specific responses in place that engage with, and emerge from, citizens ourselves. This volume takes resilience as a transformative concept to ask where and what architecture might contribute. Bringing together cross-disciplinary perspectives from architecture, urban design, art, geography, building science and psychoanalysis, it aims to open up multiple perspectives of research, spatial strategies and projects that are testing how we can build local resilience in preparation for major societal challenges, defining the position of architecture in urban resilience discourse.